2001
DOI: 10.1073/pnas.071054698
|View full text |Cite
|
Sign up to set email alerts
|

Role of the arginine-nitric oxide pathway in the regulation of vascular smooth muscle cell proliferation

Abstract: This contribution is part of the special series of Inaugural Articles by members of the National Academy of Sciences elected on April 27, 1999.The objective of this study was to elucidate the mechanisms by which nitric oxide (NO) inhibits rat aortic smooth muscle cell (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
227
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(246 citation statements)
references
References 30 publications
14
227
1
4
Order By: Relevance
“…This activity of NO ⅐ has been ascribed to both cGMP-dependent and -independent mechanisms. Experiments in rodents have found, with a few notable exceptions (18,30), that NO ⅐ controls the cell cycle through cGMP. In contrast, the anti-proliferation effects of NO ⅐ in human cells have been more frequently associated with cGMP-independent signaling (29,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This activity of NO ⅐ has been ascribed to both cGMP-dependent and -independent mechanisms. Experiments in rodents have found, with a few notable exceptions (18,30), that NO ⅐ controls the cell cycle through cGMP. In contrast, the anti-proliferation effects of NO ⅐ in human cells have been more frequently associated with cGMP-independent signaling (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO ⅐ ) regulates a wide range of cellular activities including gene expression (12)(13)(14)(15)(16), cell proliferation (17,18), and apoptosis (19) that are closely linked to its anti-tumor and anti-atherosclerotic properties (17,20). Using a microarraybased approach in soluble guanylate cyclase-deficient cells, we recently demonstrated that NO ⅐ predominately regulated a large set of cell cycle genes independent cGMP (15).…”
mentioning
confidence: 99%
“…Arginase I is considered the hepatic isoform catalyzing the final step in the urea cycle, and its expression can be induced by hypoxia and lipopolysaccharide 5. Arginase II, as the extrahepatic isoform, is the principal form in human and mouse aortic endothelial cells (ECs) and provides L‐ornithine for the synthesis of polyamines, putrescine, spermidine, and spermine (SPM), associated with cell proliferation and differentiation 6, 7. Arginase II is also inducible by hypoxia, lipopolysaccharide, and tumor necrosis factor‐α,8, 9, 10 and increased arginase II activity in ECs has recently been extended to other disorders in animal models, including aging,11 ischemic reperfusion,12, 13 hypertension,14, 15 balloon injury,16 and atherosclerosis 2.…”
mentioning
confidence: 99%
“…Recently, Ignarro and coworkers (5,6) showed that nitric oxide (NO) is capable of inhibiting the proliferation of rat aortic smooth muscle cells in a cGMP-independent pathway. The cytostatic action of NO was attributed to its inhibitory effect on ornithine decarboxylase, an enzyme that generates spermine, spermidine, and putrescine, which are required for cell proliferation.…”
mentioning
confidence: 99%